Efficient olfactory coding in the pheromone receptor neuron of a moth - Kostal, Lubomir; Lansky, Petr; Rospars, Jean-Pierre (PLoS computational biology, 2008)
The concept of coding efficiency holds that sensory neurons are adapted, through both evolutionary and developmental processes, to the statistical characteristics of their natural stimulus. Encouraged by the successful invocation of this principle to predict how neurons encode natural auditory and visual stimuli, we attempted its application to olfactory neurons. The pheromone receptor neuron of the male moth Antheraea polyphemus, for which quantitative properties of both the natural stimulus and the reception processes are available, was selected. We predicted several characteristics that the pheromone plume should possess under the hypothesis that the receptors perform optimally, i.e., transfer as much information on the stimulus per unit time as possible. Our results demonstrate that the statistical characteristics of the predicted stimulus, e.g., the probability distribution function of the stimulus concentration, the spectral density function of the stimulation course, and the intermittency, are in good agreement with those measured experimentally in the field. These results should stimulate further quantitative studies on the evolutionary adaptation of olfactory nervous systems to odorant plumes and on the plume characteristics that are most informative for the 'sniffer'. Both aspects are relevant to the design of olfactory sensors for odour-tracking robots.
Keywords: sexuální lákadla; akční potenciály; Olfactory Receptor Neurons; Models, Neurological; Computer Simulation; Action Potentials; Smell; Olfactory Pathways; Moths; počítačová simulace; mužské pohlaví; Sex Attractants; můry; čichové dráhy; ženské pohlaví; zvířata; čichové buňky; modely neurologické; čich; Female; Male; Animals